Bridging Technology and Pedagogy: AI Integration in ESP Teaching and Lecturer Readiness in Higher Education Institutions - Hamidah, Fitria Nur; Dja’far, Veri Hardinansyah (JOLLT Journal of Languages and Language Teaching, 2026)
Although the integration of Artificial Intelligence (AI) in higher education is increasingly developing, research that simultaneously examines student perceptions, classroom practices, and lecturer readiness in the ESP context in developing countries remains limited. This study aims to analyze the effect of AI integration on ESP learning effectiveness, identify implementation challenges, and evaluate lecturers’ pedagogical and ethical readiness. Using an explanatory sequential mixed-method design, this study involved 57 non-English major students in the quantitative phase, followed by interviews with 6 ESP lecturers and learning observations. The results show a strong and significant positive correlation between perceptions of AI use and ESP learning effectiveness (r = 0.712; p < 0.01). AI has the most impact on reading comprehension (M = 4.00) and ease of access to materials (M = 3.98). Qualitative findings identified four main themes: low critical digital literacy among students, minimal ethical awareness, suboptimal pedagogical readiness of lecturers, and limitations in institutional policies and infrastructure. These findings confirm the importance of institutional AI policies, ethics-based lecturer training, and strengthening digital literacy to support effective and responsible AI integration in ESP learning.